2020
DOI: 10.1177/0003319720958554
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Timing of Foot Tissue Resection on Outcomes in Patients Undergoing Revascularization for Chronic Limb-Threatening Ischemia

Abstract: The objective of this study is to describe utilization of revascularization and tissue resection in patients with chronic limb-threatening ischemia (CLTI) and determine whether the timing of resection impacts outcomes. Revascularizations for CLTI were queried (ACS-NSQIP 2011-2015). Outcomes included 30-day major adverse limb events (MALE), major adverse cardiac events (MACE), length of stay (LOS), operative time, 30-day readmissions, and wound infections. Groups included revascularization alone, revascularizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Some authors advocate early primary closure or concurrent foot tissue resection (including debridement and minor amputations) after revascularization for CLTI. 11 , 12 ) We have focused on the wound management of toe ulcers after revascularization for CLTI. Our study showed that better wound healing after revascularization was achieved by early closed toe amputation for suspected osteomyelitis compared with conservative treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors advocate early primary closure or concurrent foot tissue resection (including debridement and minor amputations) after revascularization for CLTI. 11 , 12 ) We have focused on the wound management of toe ulcers after revascularization for CLTI. Our study showed that better wound healing after revascularization was achieved by early closed toe amputation for suspected osteomyelitis compared with conservative treatment.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 ) However, there is a paucity of evidence of primary closure of toe amputation for foot lesions associated with CLTI. 11 , 12 ) Fourth, higher levels of amputation such as transmetatarsal amputation (TMA) or BK amputation may achieve better healing rates than toe amputation for foot lesions associated with CLTI, but these could also result in loss of walking ability. In a previous study, it was found that the ability to walk was maintained by 98% of patients with CLTI who underwent toe amputation compared with 86% of those who underwent TMA and 33% of those who underwent BK amputation.…”
Section: Introductionmentioning
confidence: 99%